Performance Analysis and Design of a Robotic Fish for In-Water Monitoring - Wenwen Yuan; Shaonan Hao; Zhiqiang Liu; Feng Zhou; Youchao Wu (Journal of Marine Science and Engineering, 2025)
Compared with real fish, bionic fish have significant gaps in terms of swimming speed and efficiency, turning performance, and agility. The complicated underwater working environment necessitates monitoring equipment that can deal with the dynamic interference of dense fish schools and aquatic vegetation. An agile and flexible bionic fish with a fast swimming speed would be better suited to underwater monitoring tasks. In this study, a bionic greenfin fish robot is designed in detail, and a hydrodynamic simulation analysis of the designed bionic greenfin fish robot is carried out using STAR CCM+ and Fluent software to analyze the effects of different parameters on the propulsion performance of the pectoral fins, the steering of the caudal fins, and the emergency stop function. The swimming efficiency was found to be highest when the angle of attack was changed sinusoidally by 10° and the frequency was the same as that of the pectoral fin flutter. The feasibility of an emergency stop of the tail fin with negative-phase swinging and the adjustment of the pectoral fin uneven flutter monitoring position were also confirmed.